INFLUENCE OF CULEX FATIGANS AND GOAT LIVER AS FOOD ON FLESH PRODUCTION IN MACROPODUS CUPANUS - Manoharam, Joycy Jay (Indian Journal of Fisheries, 2011)
Chosing three different size groups of the fish Macropodus cupanus theflesh production fias been studied by providing goat liver and Ciilex futigims lasfood. Maximum flesh production was found in large-size fish when fed ad ibitumwith Culex fatigans. There is a decrease in the rate of feeding, assimilation andconversion with an increase in the body weight of the fish. Fish cultured withgoat liver as food displayed more assimilation efficiency than those fed onC. fatigans. Fish fed on C. fatigans. showed maximum specific growth and fleshproduction.